Hoarding pet animals in obsessive-compulsive disorder. Issue 1 (31st October 2014) - Campos-Lima, André L.; Torres, Albina R.; Yücel, Murat; Harrison, Ben J.; Moll, Jorge; Ferreira, Gabriela M.; Fontenelle, Leonardo F.
Abstract : Background: Although severe hoarding symptoms have been considered rare among obsessive-compulsive disorder (OCD) samples, the prevalence of animal hoarding in OCD is unknown. To help clarifying this issue, we searched for cases of animal hoarding among patients attending a university OCD clinic ( n =420). Methods: Chart review. Results: Only two patients from our sample exhibited animal hoarding (<0.5%) and only one of them presented additional obsessive-compulsive symptoms. Both cases also collected inanimate objects, presented low insight, exhibited poor response to serotonin reuptake inhibitors and did not adhere to therapy. Conclusions: There seems to be a lack of relationship between animal hoarding and OCD. However, further studies with larger numbers of patients are needed to better define their psychopathological profile and more appropriate nosological insertion.